2018
DOI: 10.1111/ene.13624
|View full text |Cite
|
Sign up to set email alerts
|

Pain in Parkinson's disease: facts and uncertainties

Abstract: Pain is one of the most common and troublesome non-motor symptoms of Parkinson's disease (PD). It can appear at any time during the disease and is often present before diagnosis. However, there is little or no consensus on its definition. An expert group of clinicians with relevant research experience met to review the existing evidence and to identify gaps in our understanding leading towards AUTHOR: 'understanding towards' has been changed to 'understanding leading towards'. Please check and confirm that thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 97 publications
1
59
0
6
Order By: Relevance
“…We found no difference in relation to headache frequency (days/3 months) and the different stages of the disease (Hoehn and Yahr scale: 2 and 2.5, headache frequency (median): 0.5 (0.5, 7.5) vs Hoehn and Yahr scale >2.5, headache frequency (median): 0.5 (0.5, 8.0); P = .757; Mann-Whitney test). We also did not find any difference in relation to the different stages of the disease and headache intensity (Hoehn and Yahr scale: 2 and 2.5, headache intensity (median): 5 (4, 8) vs Hoehn and Yahr scale >2.5, headache intensity (median): 5.5 (4,9); P = .514; Mann-Whitney test). Figure 1 shows the relationship between the severity of motor symptoms and the severity of the headache.…”
Section: Resultsmentioning
confidence: 49%
See 2 more Smart Citations
“…We found no difference in relation to headache frequency (days/3 months) and the different stages of the disease (Hoehn and Yahr scale: 2 and 2.5, headache frequency (median): 0.5 (0.5, 7.5) vs Hoehn and Yahr scale >2.5, headache frequency (median): 0.5 (0.5, 8.0); P = .757; Mann-Whitney test). We also did not find any difference in relation to the different stages of the disease and headache intensity (Hoehn and Yahr scale: 2 and 2.5, headache intensity (median): 5 (4, 8) vs Hoehn and Yahr scale >2.5, headache intensity (median): 5.5 (4,9); P = .514; Mann-Whitney test). Figure 1 shows the relationship between the severity of motor symptoms and the severity of the headache.…”
Section: Resultsmentioning
confidence: 49%
“…These patients could have different causes of pain such as musculoskeletal pain, dystonia-associated pain, and peripheral or central neuropathic pain. 3,4 This pain can occur at any time during the disease and it has a high impact on quality of life. 3,4 Despite this high prevalence of pain, only a few studies have addressed the headaches of these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease‐related pain is one of the most common and disabling phenomena in PD patients, but it is still an under‐diagnosed and under‐treated symptom because its origin is difficult to define . Recent findings on a very large sample suggested that 85% of PD patients have pain symptoms, with about 40% of patients presenting moderate to severe pain .…”
Section: Introductionmentioning
confidence: 99%
“…Occurring from the prodromal to the palliative stages of PD, a range of sleep disorders and subtypes of pain are prevalent non-motor symptoms of Parkinson's disease (PD). [1][2][3][4][5] Sleep dysfunction, which affects 60 to 98% of PD patients, may be manifested as insomnia, sleep disruption, sudden onset of sleep, rapid-eye-movement (REM) sleep behavior disorder, non-REM parasomnias, and restless legs syndrome. [6][7][8] Surveys suggest that insomnia affects 46% of PD patients; vivid dreams, 34%; acting out while dreaming, 36%; and restless legs syndrome, 42%.…”
Section: Introductionmentioning
confidence: 99%